Kontribusi Aktor Non Negara dalam SDGs: Studi mengenai Schoters dalam Pembelajaran Berbasis Digital di Indonesia - Alia, Nadya Fitri; Dermawan, Windy (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
Quality education is a key factor in achieving sustainable development, yet Indonesia continues to face challenges related to inequality in access, regional disparities, and limitations in formal education resources. In this context, non-state actors like Schoters play a relevant role by introducing innovations in non-formal, technology-based education. This study aims to explore how Schoters contributes to the achievement of Sustainable Development Goal (SDG) 4: inclusive, equitable, and quality education. Using a descriptive qualitative approach, data were collected through semi-structured interviews and online document analysis. The findings indicate that Schoters successfully builds a digital learning ecosystem through mentorship, structured learning plans, and interactive consultation services, reflecting the three key interactions in online learning communities. Moreover, Schoters’ initiatives indirectly support the alleviation of poverty (SDG 1) and the provision of decent work and economic growth (SDG 8) by opening access to international education and career opportunities. Community-based strategies, cross-subsidization, and the use of digital platforms have helped Schoters extend its educational reach. This study concludes that innovation by non-state actors can complement public policy in supporting sustainable education transformation in Indonesia.